Tuberculosis of Bones and Joints in Orthopedic - Abdul Hannan, Muhammad Bilal, Muhammad Shakeel Basit, Asifa Karamat, Muhammad Adeel Abbas, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Mycobacterium Tuberculosis (TB) is a major global health concern and burden on developing countries economy. Pakistan ranks in top 10 countries of the world with high load of TB and a big chunk of this disease process is extra pulmonary TB (EPTB). Among extra pulmonary sites, is bone and joint TB is very common yet under reported. Recent literature has found up to 35% of all extra pulmonary cases are bone and joint TB. Purpose: We aim to do an analysis of frequency of bone and joint TB in our institution in all new patients getting registered for treatment of TB. Methodology: This was retrospective analysis 8 years of Data collected in Gulab Devi Hospital Lahore. Data was analyzed using Microsoft excel software and results are tabulated. Findings: Total number of new registered patients of Extra-pulmonary Tuberculosis (EPTB) were 13000 (20%). Out of these EPTB patients, bone and joint TB diagnosis was made in 690(5.3%) patients. Out of these 690 patients, 400 (58%) cases were recorded in Indoor facility and 290 (42%) cases were seen in outdoor facility. Most common site is Spine 340 cases (85%) followed by Hip joint 16 cases (4%), knee joint 12 cases (3%) and upper limb 16 cases (4%). Practical Implication: Regarding management of newly registered cases, Gulab Devi hospital is working in collaboration with world Health Organization TB control program and Provincial TB control Program Punjab (PTP). All new cases are managed by multi-disciplinary team and after initial registration are referred to their relevant specialties. Conclusion: Axial skeleton remains the most common site in al literature and so is the conclusion of our analysis. Detailed research work is still needed in several aspects of this ancient disease to reduce the morbidity and mortality associated with it. Keywords: Bone and joint TB, Pulmonary Tuberculosis, Extra pulmonary Tuberculosis